Analisis Isi Pesan Persuasif Nilai Kebersamaan Dalam Kampanye “Ya Kali Gak Lanjut” Pada Akun Instagram @fanta_id - Fauzi Syarief; Venessa Agusta Gogali; Yogi Ariska (Jurnal Public Relations (J-PR), 2026)
This study aims to analyze the content of persuasive messages regarding the value of togetherness in the “Ya Kali Gak Lanjut” campaign on the @fanta_id Instagram account using the Elaboration Likelihood Model (ELM) developed by Richard E. Petty and John T. Cacioppo. This research employs a qualitative approach with a content analysis method to examine campaign content in the form of carousel posts consisting of visuals, text, slogans, and captions published on the @fanta_id Instagram account. The data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that the persuasive messages in the “Ya Kali Gak Lanjut” campaign utilize two persuasion routes, namely the central route and the peripheral route. The central route is reflected in messages that associate Fanta products with various togetherness activities during Ramadan, such as breaking the fast, gathering after Tarawih prayers, playing with friends, and watching movies together. Meanwhile, the peripheral route is more dominant through the use of attractive visuals, the brand's distinctive colors, the slogan "Yakali Gak Mau Fanta," popular language that resonates with young audiences, and representations of togetherness that foster emotional closeness with the audience. The findings indicate that Fanta's persuasive communication strategy emphasizes an emotional branding approach by positioning the product as an integral part of togetherness during Ramadan rather than relying on rational arguments about the product's advantages. Therefore, the value of togetherness serves as the campaign's primary persuasive message, strengthening the brand image while enhancing the campaign's appeal on social media.